Towards Comprehensive Newborn Hearing and Genetic Screening in Russia: Perspectives of Implementation - Svetlana Chibisova; Tatiana Markova; Evgenia Tsigankova; George Tavartkiladze (MDPI AG, 2024)
The universal newborn hearing screening (NHS) program was implemented in Russia in 2008 to replace the high-risk newborn hearing screening. More than 95% coverage and significant improvement in early detection and intervention is achieved. Meanwhile, it was shown that current OAE-based hearing screening missed 13% of newborns with genetically ascertained hereditary sensorineural hearing loss (SNHL). The aim of the study is to assess the results of genetic investigation and NHS in a large cohort of Russian children with bilateral SNHL and to study the feasibility of implementation of combined hearing and genetic screening in Russia. Genetic, audiological and NHS data of 1292 pediatric patients with bilateral SNHL born in 2008-2021 were analyzed. GJB2 sequencing was performed for all subjects, 644 patients had pathological GJB2 genotype, 406 of them were homozygous for c.35delG variant. The group of 155 GJB2-negative patients were searched for other SNHL genes, The pathological genotypes were identified at 87 patients. The most frequent genes were STRC (21.8%), USH2A (16.1%), OTOF (8%) and SLC26A4 (6.9%). Children with confirmed genetic etiology passed NHS in 21% of cases. The perspectives of implementation of national comprehensive newborn hearing and genetic screening including whole exome sequencing technologies are discussed.